Characteristics of Partner Violent Perpetrators and Factors Involved in Their Violent Behavior - Maljković, Marija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Violence in intimate partner relationships is a widespread phenomenon and is the most common type of victimization of women by domestic violence. It signifies a violation of women's human rights and forms of discrimination against women, and given the complexity and harmfulness of consequences, it is a serious social problem. Prejudice and lack of information about violence against women help, encourage and justify violence and influence how (and whether in general) a woman will recognize violence and react to it, so it is important to find out the facts about violence. Identifying, revealing and overcoming these prejudices is one of the first steps in ending violence against women. That is why the subject of this work is the characteristics of the partners of the partner violence, and the aim is to find out more about the characteristics and factors that contribute to violent behavior.